THE COMPETENCE OF THE EUROPEAN UNION INSTITUTIONS IN THE FIELD OF ENVIRONMENTAL PROTECTION - Ştefan Ciprian Raicea (PEOPLE: International Journal of Social Sciences, 2025)
The emergence of competence in the field of environmental protection was a catalyst for the comprehensive agenda in this matter that the EU has developed since then. The interpretation of this competence by the Court of Justice of the European Union (CJEU), as well as the jurisprudential development of the principles regarding environmental protection, were essential in the development of the Union’s environmental acquis. Other environmental policy implementation tools such as programmes, Commission communications, strategies and white papers also play an important role even if they are recommendations.The core of EU environmental law is strongly influenced by the principles listed in Article 191(2) TFEU, which states that Union policy shall be based on the precautionary principle and on the principles that preventive action should be taken, that environmental damage should as a priority be rectified at source and that the polluter should pay. Each of these principles is detailed separately. In short, the precautionary principle aims to minimise damage caused by unknown environmental risks. The preventive action principle aims to minimise damage caused by known environmental risks, the source principle seeks to prevent further damage by addressing the source of the environmental problem, and the polluter pays principle aims to ensure that the damage falls on those involved in a polluting activity.